2014
DOI: 10.1159/000441052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluoride on the Expression of Beclin1 and mTOR in Ameloblasts

Abstract: Exposure to high levels of fluoride (F-) can result in dental fluorosis in different individuals, but the mechanism of dental fluorosis remains unclear. Autophagy is a highly conserved intracellular digestion process that degrades damaged organelles and protein aggregates. This study examined the effect of sodium fluoride (NaF) on the expression of Beclin1 and mTOR to elucidate the development mechanisms of dental fluorosis. HAT-7 cells were incubated with various concentrations of NaF, and autophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
(28 reference statements)
3
20
0
1
Order By: Relevance
“…Recently, it was demonstrated that uoride also induces autophagy due to an increased expression of Beclin1 and LC3 and a decreased expression of p62 in osteoblasts [17,45]. Similarly, a dose-response pattern in LC3-II protein expression in ameloblastderived cells has been observed with uoride treatment [30], which decreases after increasing the concentration of uoride. The present study demonstrated that NaF treated groups had increased mRNA and protein expression levels of p62 and suppressed levels of Beclin1 (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Recently, it was demonstrated that uoride also induces autophagy due to an increased expression of Beclin1 and LC3 and a decreased expression of p62 in osteoblasts [17,45]. Similarly, a dose-response pattern in LC3-II protein expression in ameloblastderived cells has been observed with uoride treatment [30], which decreases after increasing the concentration of uoride. The present study demonstrated that NaF treated groups had increased mRNA and protein expression levels of p62 and suppressed levels of Beclin1 (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…This further indicates that periodontal cells are less sensitive to autophagy. Lei et al demonstrated that high uoride could cause autophagy of HAT-7 cells, especially related to the expression of Beclin1 [30]. It has also been postulated that the regulation of p62 is responsible for controlling the formation of intracellular inclusion bodies in autophagy, and Beclin1 is involved in the initial steps of the formation of autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of beclin1, which is required for autophagosome formation, decreases the expression of mTOR increased at 1.2 mmol/l NaF (25). Fluoride promoted cytochrome-c release, up-regulation of UCP2, attenuation of ATP synthesis, and H2AX phosphorylation (γH2AX) as far as DNA damage and cell death (18).…”
Section: In Vitro Studiesmentioning
confidence: 98%
“…Estas dos últimas, marcadores de los ameloblastos en la etapa de maduración (Kawano et al 2002). Estas células también han sido usadas con el propósito de conocer el papel de la autofagia en la fluorosis dental y sus mecanismos de acción (Lei et al 2015). Sin embargo, se requieren más estudios para determinar si las células epiteliales de rata pueden servir como un modelo optimo que permita conocer los roles fisiopatológicos de los ameloblastos a lo largo de su proceso de diferenciación y el papel de factores que modifiquen una adecuada formación del esmalte dental.…”
Section: Impacto Da Concentração De Soro Bovino Fetal Nas Células Epiunclassified